Blended Learning Through Learning Manajement System In Mathematic Of Statistic And Opportunity : Students’ Perception - Ahmad Ahmad; Heny Sri Astutik (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2023)
During the COVID-19 pandemic, the conventional education revolution to technology-based education became the world’s spotlight. Online learning activities are one of the most effective solutions during the COVID-19 pandemic. Learning has begin to transition from face-to-face learning to distance learning (online learning) through. Blended learning activities are one of the best options thet can be implemented after the COVID-19 pandemic situation. Student perceptions have a significant part in enhancing students' role, activeness, and progress during the learning process in order to attain learning objectives. As a result, the goal of this research was to find out how senior high school students perception about blended learning though LMS in mathematics. This study employs descriptive quathitative methods with 47 sudents of grade IX in one of SMP Negeri at Sokaraja as a respondent of the study. Questionaire was used to collect the data. According to the findings of the study, Class IX students' perceptions of online learning in subjects Mathematics in the Covid-19 Pandemic at SMP Negeri 2 Sokaraja are in moderate category with a percentage of 6. percentage of 42.56%.